Method of manufacturing multilayer graphene coated nanoscale silicon anode active materials and secondary battery using the same
Patent Information
- Application Number
- KR1020230195922
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2043-12-29
Smart Images

Figure 112023147391341-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a nanoscale silicon negative electrode active material coated with multilayer graphene and a secondary battery using the same, and more specifically, to a technology for manufacturing a secondary battery negative electrode active material by coating nanoscale silicon particles with an adhesive slurry. Background Technology
[0002] Electric energy produced from a wide range of sources, including fossil fuels, nuclear power, wind, hydroelectric, and solar power, has a structure that optimizes only when production and consumption match. In other words, since large-scale storage of electrical energy has limitations, its use is restricted in areas where power transmission is difficult.
[0003] Recent groundbreaking advancements in secondary batteries have made it possible to store electrical energy in large capacities sufficient to power not only simple portable devices but also automobiles.
[0004] The portability and mobility of secondary batteries offer various advantages; on roads, they are eco-friendly, and by localizing power plants, they can be considered advantageous for economically solving pollution problems.
[0005] In fact, several countries are researching ways to supply electricity when needed by charging ESS devices directly at power plants, and there is a demand for larger capacity secondary batteries.
[0006] Commercially successful secondary batteries consist of a structure of a lithium anode, a graphite anode, an electrolyte, and a separator, and the anode and cathode determine the capacity. The lithium anode is being improved to increase capacity by mixing it with nickel, chromium, magnesium, aluminum, etc., to increase capacity per unit area, and the graphite anode is made of natural graphite, artificial graphite, or a mixture thereof.
[0007] Graphite as a cathode material has a theoretical capacity of 320 mWh / g, but since it is expected to soon reach a technical limit capacity of about 250 mWh / g in currently produced secondary batteries, there have been attempts to develop new cathode active materials, and the materials closest to commercial viability are lithium metal cathodes and silicon cathodes.
[0008] The biggest disadvantage of lithium metal anodes is lithium dendrites growing on the anode, while the biggest disadvantage of silicon is expansion when charged. Attempts are being made to solve the lithium dendrites problem through various polymer coatings, and silicon expansion is being attempted through nanosilicon, the matrixing of nanosilicon, pores, carbon coatings, etc.
[0009] When using a graphite anode, the principle is that lithium enters between the atomic layers of the layered graphite structure during charging and returns to the anode during discharging; in contrast, with a silicon anode, the principle is that lithium breaks the bonds between silicon atoms during charging and returns to the anode during discharging.
[0010] The theoretical charge capacity of silicon anodes is 3400 mWh / g, and they have superior physical properties compared to graphite. Therefore, due to various technical requirements, silicon is the material selected as the top priority in research and development for anode applications.
[0011] Currently, silicon faces several challenges in being applied to commercially produced secondary battery structures, but significant technological advancements are being made regarding the most critical issue: silicon expansion.
[0012] The physical principle of expansion is that when lithium atoms are charged into the negative electrode, the graphite negative electrode active material is located in the center of the six-atom structure of graphite and shows an expansion rate of about 10%, whereas silicon has a structure where lithium atoms penetrate between silicon bonds and form an alloy with silicon, showing an expansion rate of about 300%.
[0013] If a high expansion rate is used in the manufacture of a secondary battery, repeated charging and discharging will destroy the negative electrode, causing the battery cell to stop functioning.
[0014] Solutions to silicon expansion in secondary batteries are largely being attempted by applying principles such as directly increasing the silicon surface area or reducing the number of silicon bonds using very small nano-silicon, silicon nanowires, or porous silicon.
[0015] In addition to these methods, there are techniques such as synthesizing porous carbon to grow nanosilicon in its pores and controlling nanosilicon using a binder, but these are still in the technology development stage of the production process.
[0016] Patent Document 1 has disadvantages in terms of process difficulties and economic feasibility, such as the need to separately synthesize a large quantity of porous carbon molds and to grow nano silicon in the pores using silane (silicon hydride) PECVD.
[0017] Patent Document 2 describes a method of coating graphene by spraying it onto a silicon slurry, which is inefficient compared to the mechanism in which graphene is used as a conductive material in the cathode manufacturing process. Prior art literature
[0018] US Registered Patent US10,147,950, Korean Registered Patent No. 10-1634728 The problem to be solved
[0019] The present invention aims to solve the above-mentioned problems by providing a method for manufacturing a secondary battery negative electrode active material by coating nano-sized silicon particles with an adhesive slurry, and a secondary battery using the same. means of solving the problem
[0020] A method for manufacturing a nano-sized silicon negative electrode active material coated with multilayer graphene according to the present invention for the above-mentioned problem to be solved comprises the steps of: preparing a graphene precursor compound; preparing an adhesive slurry by mixing a thinner with the graphene precursor compound; preparing a composite slurry by mixing the adhesive slurry with nano-sized silicon; drying the composite slurry; and calcining the dried composite slurry in a kiln.
[0021] The above nanoscale silicon particles are characterized by having a diameter of 50 nm to 1000 nm.
[0022] The above drying step is characterized by being performed at a low temperature of 10°C to 90°C to prevent oxidation of nano-sized silicon.
[0023] The above firing step is characterized by being performed at a high temperature of 900℃ to 1500℃.
[0024] The above composite slurry is characterized by containing 10 to 90% by weight of nano-sized silicon in the adhesive slurry.
[0025] The step of preparing the graphene precursor compound is characterized by mixing 60-75 wt% xylene, 10-15 wt% ethylene benzene, 5-10 wt% nitrogen-substituted aromatic molecule, 1-5 wt% carbon black, 1-5 wt% zinc compound, 1-5 wt% amide, and 0.1-0.9 wt% toluene.
[0026] The adhesive slurry is characterized by being composed of the graphene precursor compound and thinner in a weight ratio of 1:1.5 to 1:9.
[0027] The above thinner is characterized by containing 50-60% toluene, 20-30% acetone, and 10-20% butyl cellosolve by weight.
[0028] The above firing is characterized by a heating rate of 2°C to 5°C per minute in an inert gas atmosphere.
[0029] It is characterized by grinding the composite slurry into a size used for manufacturing a cathode active material after drying or calcination.
[0030] In another embodiment of the present invention, a nanoscale silicon negative electrode active material coated with multilayer graphene is prepared by a method for preparing a nanoscale silicon negative electrode active material coated with multilayer graphene.
[0031] The graphene-coated nanoscale silicon is characterized by being silicon carbide in which one or more silicon atoms are aggregated within the multilayer graphene.
[0032] Another embodiment of the present invention is a secondary battery manufactured using a nanoscale silicon negative electrode active material coated with multilayer graphene. Effects of the invention
[0033] The nanoscale silicon anode active material coated with multilayer graphene according to the present invention has nanoscale silicon embedded within the graphene, which suppresses expansion—a disadvantage of silicon anodes—thereby preventing the anode from being destroyed by expansion.
[0034] The adhesive xylene slurry used as a precursor for graphene formation according to the present invention has the effect of preventing the graphene and silicon core from being released during calcination.
[0035] The adhesive xylene-coated nanoscale silicon slurry of the present invention has the advantage that graphene is uniformly formed on a single silicon particle or a mixture of two or more silicon particles because it is dried at a low temperature, ground into granules, and then calcined.
[0036] The present invention has a cost-saving effect because it is coated with multiple layers of highly conductive graphene, allowing the carbon conductive material to be omitted when coating a silicon negative electrode active material onto a negative electrode current collector.
[0037] When mixed with graphite active material, which is the negative electrode active material used in existing commercial processes, it can be used as a substitute for a conductive material that increases electrical conductivity and has the effect of improving the capacity of secondary batteries.
[0038] The method for manufacturing a nano-sized silicon active material coated with multilayer graphene according to the present invention is advantageous for increasing productivity because the process is simple since it uses a carbon-based adhesive slurry to mix with silicon. Brief explanation of the drawing
[0039] Figure 1 is a schematic diagram and photograph showing a nanoscale silicon active material coated with multilayer graphene according to the present invention. FIG. 2 is a flowchart of a method for manufacturing a nanoscale silicon active material coated with multilayer graphene according to the present invention. Figure 3 is a photograph showing the results of the manufacturing process of a nanoscale silicon active material coated with multilayer graphene according to the present invention. Figure 4 shows a photograph and Raman spectrum of a nanoscale silicon active material coated with multilayer graphene. Specific details for implementing the invention
[0040] The present invention will be described below with reference to specific embodiments and drawings for implementation. The embodiments of the present invention are intended to illustrate a single invention, and the scope of the rights is not limited to the illustrative embodiments. Furthermore, the illustrative drawings should not be interpreted as being limited to the drawings, as they only illustrate the essential details and omit incidental details for the clarity of the invention.
[0041] The present invention uses an adhesive slurry as a graphene precursor to be combined with nanoscale silicon, and by drying and firing, silicon particles coated with multiple layers of graphene are obtained and used as a negative electrode active material for a secondary battery.
[0042] FIG. 2 is a flowchart of a method for manufacturing a nano-sized silicon active material coated with multilayer graphene according to the present invention, comprising the steps of: manufacturing a graphene precursor compound; manufacturing an adhesive slurry by mixing a thinner with the graphene precursor compound; manufacturing a composite slurry by mixing the adhesive slurry with nano-sized silicon; drying the composite slurry; and calcining the dried composite slurry in a kiln.
[0043] The above adhesive slurry is a slurry containing a polymeric organic compound and may be one or more mixtures of copolymers selected from xylene, polystyrene monomer, polystyrene oligomer, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene fluoride, and polyhexafluoropyrene. In the present invention, xylene is preferably used.
[0044] The adhesiveness of the adhesive slurry is obtained by adding a small amount of acetone, NMP (N-Methyl-2-pyrrolidone), acrylic, etc.
[0045] Nanoscale silicon has a size of about 50 nm to 1000 nm and is preferably spherical, but does not necessarily have to be spherical.
[0046] The step of preparing a graphene precursor compound involves mixing 60-70 wt% xylene, 10-15 wt% ethylbenzene, 5-10 wt% nitrogen-substituted aromatic polymer, 1-5 wt% carbon black, 1-5 wt% zinc complex, 1-5 wt% amide, and 0.1-0.9 wt% toluene.
[0047] The adhesive slurry is prepared by adding a thinner to the above graphene precursor compound to dilute and mix it.
[0048] The thinner consists of 50–60% toluene, 20–30% acetone, and 10–20% butyl cellosolve by weight.
[0049] The adhesive slurry is diluted by adding thinner to a graphene precursor compound; the graphene precursor compound to thinner is mixed in a weight ratio of 1:1.5 to 1:9 and continuously mixed using a low-speed impeller. The acetone component of the thinner imparts adhesiveness to the polymer xylene. The mixing ratio of the adhesive slurry and thinner can be selected differently depending on the size of the particles to be coated.
[0050] The mixing ratio of the adhesive slurry and the thinner can be selected and used differently depending on the number of layers of the multilayer graphene.
[0051] A composite slurry, which is a xylene-coated nano-sized silicon slurry, is prepared by adding nano-sized silicon in a weight ratio of 10 to 90% to an adhesive slurry.
[0052] The composite slurry is stirred at room temperature to evaporate about 70% to 90% of the solvent, and then dried under vacuum at 40 to 90°C. It is advantageous for the process to select a relatively low drying temperature to prevent silicon oxidation.
[0053] The dried composite slurry is crushed into granules, placed in a crucible, and calcined in a kiln.
[0054] Xylene-coated nanoscale silicon granules can be single granules or aggregated into two or more.
[0055] The temperature of the dried xylene-coated nanoscale silicon calcination process is 900°C to 1500°C for 1 to 4 hours. At this time, a heating rate of about 1°C to 5°C per minute is suitable.
[0056] The calcination process is carried out in an Ar, H2 gas atmosphere, or a mixture thereof. The pressure starts from atmospheric pressure and goes up to 1x10 -6 It is set to a vacuum of torr. If process safety is the top priority, a mixed gas of Ar (95%) / H2 (5%) and atmospheric pressure are suitable.
[0057] The dried composite slurry may proceed directly to the calcination process without grinding. In this case, the grinding process is performed after the calcination process is finished.
[0058] Grinding is carried out by controlling the size of nano-sized silicon particles embedded in a multilayer graphene matrix to match the size of the silicon anode active material used in the anode manufacturing process.
[0059] The multilayer graphene-coated nanoscale silicon active material can be coated with graphene on a single nanoscale silicon particle or two or more particles clustered together.
[0060] Figure 1 shows a schematic diagram and a photograph of a state in which multiple nanoscale silicon active materials are aggregated and coated with multilayer graphene, and multiple nanoscale silicon is infiltrated into the multilayer graphene.
[0061] FIG. 2 is a flowchart of a method for manufacturing a nanoscale silicon active material coated with multilayer graphene according to the present invention, and FIG. 3 shows process-by-process photographs representing a composite slurry, a primary dried state, and a calcined state.
[0062] Figure 4 shows a photograph and Raman spectrum of nanoscale silicon coated with multilayer graphene. In the nanoscale silicon active material coated with multilayer graphene, graphene-coated nanoscale silicon particles may be clustered individually or in groups of two or more. In single-layer graphene, the size of the two-dimensional (2D) peak is approximately twice that of the graphite peak in Raman measurements, resulting in a significantly larger two-dimensional peak. However, as the number of graphene layers increases, the two-dimensional peak gradually decreases, eventually leaving only the graphite peak. Therefore, in Figure 4, since the two-dimensional peak is smaller than the graphite peak, it is determined to be multilayer graphene.
[0063] Nanoscale silicon particles with a diameter of 50 nm to 1000 nm are used, and porous silicon may also be used. For larger particles, using porous silicon particles increases the specific surface area, which is effective in withstanding expansion.
[0064] When porous silicon is incorporated into a multilayer graphene matrix, the protection of carbon and the specific surface area effect can be expected to withstand expansion.
[0065] In the present invention, silicon may include silicon oxide.
[0066] In the present invention, the silicon may be porous silicon.
[0067] In the present invention, porous silicon may include porous silicon oxide.
[0068] The present invention can be used to increase conductivity by coating graphene onto a graphite cathode active material.
Claims
Claim 1 A method for manufacturing a nano-sized silicon negative electrode active material coated with multilayer graphene, characterized by comprising the steps of: preparing a graphene precursor compound by mixing 60~75 wt% xylene, 10~15 wt% ethylene benzene, 5~10 wt% nitrogen-substituted aromatic molecule, 1~5 wt% carbon black, 1~5 wt% zinc compound, 1~5 wt% amide, and 0.1~0.9 wt% toluene; preparing an adhesive slurry by blending a thinner with the graphene precursor compound; preparing a composite slurry by blending the adhesive slurry with nano-sized silicon; drying the composite slurry; and calcining the dried composite slurry in a kiln to form multilayer graphene. Claim 2 A method for manufacturing a nanoscale silicon negative electrode active material coated with multilayer graphene according to claim 1, characterized in that the nanoscale silicon particles have a diameter of 50 nm to 1000 nm. Claim 3 A method for manufacturing a nano-sized silicon negative electrode active material coated with multilayer graphene according to claim 1, wherein the drying step is performed at a low temperature of 10°C to 90°C to prevent oxidation of nano-sized silicon. Claim 4 A method for manufacturing a nano-sized silicon negative electrode active material coated with multilayer graphene according to claim 1, characterized in that the calcination step is performed at a high temperature of 900℃ to 1500℃. Claim 5 A method for manufacturing a nano-sized silicon negative electrode active material coated with multilayer graphene according to claim 1, wherein the composite slurry comprises 10 to 90% by weight of nano-sized silicon in an adhesive slurry. Claim 6 delete Claim 7 A method for manufacturing a nano-sized silicon negative electrode active material coated with multilayer graphene according to claim 1, wherein the adhesive slurry is composed of the graphene precursor compound and a thinner in a weight ratio of 1:1.5 to 1:
9. Claim 8 A method for manufacturing a nano-sized silicon negative electrode active material coated with multilayer graphene according to claim 7, characterized in that the thinner comprises 50-60% toluene, 20-30% acetone, and 10-20% butyl cellosolve by weight. Claim 9 A method for manufacturing a nano-sized silicon negative electrode active material coated with multilayer graphene according to claim 1, wherein the calcination is performed in an inert gas atmosphere at a heating rate of 2°C to 5°C per minute. Claim 10 A method for manufacturing a nano-sized silicon cathode active material coated with multilayer graphene according to claim 1, characterized by grinding the composite slurry to a size used for manufacturing a cathode active material after drying or calcination. Claim 11 A nanoscale silicon negative electrode active material coated with multilayer graphene manufactured by the manufacturing method of claim 1. Claim 12 A nano-sized silicon negative electrode active material coated with multilayer graphene according to claim 11, characterized in that the graphene-coated nano-sized silicon is silicon carbide in which one or more silicon atoms are aggregated and formed within the multilayer graphene. Claim 13 A secondary battery manufactured using a nanoscale silicon negative electrode active material coated with multilayer graphene of claim 12.
Citation Information
Patent Citations
Hybrid Graphene Composite Particles
KR102545573B1
Nano silicon composite material of core-shell structure as well as preparation method and application of material
CN111816857A
Graphene-silicone microparticle and the preparation method thereof
KR1020150060459A
